Immunosuppression and mycobacteria other than Mycobacterium tuberculosis: results from patients with and without HIV infection. - Peters, M. (Cambridge University Press, 1989)
Infections caused by mycobacteria other than Mycobacterium tuberculosis (MOTT) have often been described as common in AIDS patients. To evaluate whether infections with MOTT are specific for HIV related immunosuppression or are also frequent in patients with immunosuppression of different aetiology, data on the frequency of isolation from immunosuppressed patients with HIV infection are important. Blood, stool and urine specimens from 134 patients with non-HIV related immunosuppression, and from 55 immunocompetent subjects were examined for mycobacteria. MOTT have been isolated from one immunocompetent person but from none of the immunosuppressed patients. Since in AIDS patients an initial colonization of the gastrointestinal tract (GI-tract) with MOTT is common, GI-tract biopsy specimens from an additional 80 patients were examined microscopically and histologically for mycobacteria. Mycobacteria were not isolated from these specimens. In the same period of time 72 AIDS patients have been examined; 7 (10%) had infections with M. tuberculosis whereas MOTT have been isolated from 16 (22%) of these patients. Mycobacteria have been found only rarely in immunocompetent patients and have not been isolated from patients with non-HIV related immunosuppression. The isolation of MOTT is highly correlated with an HIV-related immunosuppression.